EDUCATION FOR THE PROFESSION. - Lynn, Edward S. (The Accounting Review, 1964)
Abstract The article explains the position and activities of the American Institute of Certified Public Accountants (AICPA) regarding education and the author's views regarding the proper kind of education for the profession. AICPA has long had a vital interest in the education of public accountants because its leaders appreciate that education helps to maintain and improve the standards of the profession. It has expressed this interest by engaging in a number of activities over the years that have resulted in the approval of educational policies by the Council of the Institute. The logical starting point for a description of the Institute's educational policies that are currently in effect is the report of the Commission on Standards of Education and Experience for CPAs, issued in 1956. Though the Commission was set up at the suggestion of the American Institute, it was an independent body made up of outstanding practitioners and educators who did not represent organized groups of accountants or educators.